Values and Health-Related Behaviour: A Comparison of Youth in Hungary and Transylvania - Pikó, Bettina; Brassai, László (European Journal of Mental Health, 2007)
A Comparison of Youth in Hungary and Transylvania: A number of factors have been investigated as important determinants of adolescent health-related behaviour among which values occupy a special place. A growing number of studies of adolescents’ health-related behaviours include cultural factors. The main goal of the present study was to investigate how a set of values preferred by youth influence their healthrelated behaviours using a cross-cultural study design of samples of youth from Szeged, Hungary (N = 160), and Târgu Mureş (Marosvásárhely), Transylvania, Rumania (N = 124). Data were collected using a self-administered questionnaire. The following values were investigated: filial piety, familism, machismo, collectivism and fatalism. In addition, four health-related behaviours were measured: smoking, alcohol use, marijuana use and sports activity. Irrespective of culture, female students tend to prefer filial piety, collectivism, whereas male students reported higher scores on machismo. Male students in Hungary tend to report higher levels of marijuana use, whereas males from the Transylvanian sample report a higher engagement in sports activity. Alcohol use is more common among males in both samples. Some important cultural differences in the relationship between values and health-related behaviours may also be detected. Among youth in Hungary, fatalism is related to higher levels of substance use. Machismo, on the other hand, plays a role in higher levels of sports activity in the Transylvanian sample. Finally, preferring social values, such as filial piety, familism and collectivism, may be associated with lower levels of substance use or higher levels of sports activity, that is, a more favourable health behaviour pattern in both samples.